Networks and opportunistic urban design: a strategy for regeneration of public spaces in Lisbon - Guerreiro, Rosália (2012)
Network thinking has opened up new research fields for the understanding of the city form. Cities are not completely predicable and they are much more about self-organized networks than about rational top-down planning and design. Self-organization is a property of complex open systems and the city is not an exception. Urban development and regeneration requires new creative responses bottom-up based approaches. However a theory which creates a framework for examining self-organized cities was unavailable until recently. Using complexity theories and network thinking, the design of cities should start within an entirely new field, emerging in response to major changes in society. Also the understanding of the concepts of scale-free networks, self-similarity structures, and the process of unfolding can be utilized to understand the cities’ form and to predict and design efficiently new developments. Opportunistic urban design, invites us to consider innovative urban design solutions that respond to a specific context. This abstract focuses on the discussion of these topics in a research project that is being developed on the city of Lisbon considering the cross-referencing of its natural morphology with the city’s street movement which generates a self-organized network composed by links (streets) and nodes (plazas). The final aim is to define a pedestrian network informed by the understanding of patterns of public life which enable a public space to become a successful place. The main goal of this project is to explore opportunistic urban design solutions based on the identification of networks as a powerful structure to regenerate the city at different scales. If the propose of top-down planning is to legitimize 'what should be done', opportunistic design thinking seeks bottom-up actions of 'what can be done’ - a process of creative thinking leading to more flexible, more inventive and more contextually responsive strategies of intervention into the urban environment.